(untitled) (Research, Society and Development, 2021)
The pharmacist is responsible for monitoring the patient with tuberculosis to assess the use of drugs and possible misuses, their effect iveness and possible adverse effect son the body. Thus, the study sought to carry out na integrative review on the role of the pharmacist in the care of patient swith tuberculosis and asking: "What does the literature show about the role of the pharmacist in the care of patient swith tuberculosis?" The search for articles was performed in the following databases: LILACS (Latin American and Caribbe na Literature in Health Sciences), MEDLINE (Medical Literature Analysis), IBECS (Spanish Bibliographic Index in Health Sciences), BDENF (Database in Nursing), Scientific Electronic Library Online (SCIELO) and CAPES Journal Portal (PPC). Using the descriptors in Health Sciences (DeCS): Multiple Drug-Resistant Tuberculosis and the irrespective synonyms; Pharmaceutical care; Quality of Health Care; Antituberculosis; Mycobacterium tuberculosis; Pulmonary Tuberculosis; tuberculosis; Multiple Bacterial Drug Resistance. A total of 1112 publications were collected for screening, of which 5 were included in the integrative review. The studies carried out, they addressed pharmaceutical care in the care of patients with tuberculosis, investigated the knowledge of pharmacists about tuberculosis and evaluated the pharmaceutical services provided in Primary Health Care. The pharmacist needs to know about the disease, its therapeutics chemes, drug interactions and adverse reactions, however, the lack of publications related to the topic was pointed out and this highlights the need for the pharmacist’s engagement to contributed to eradication of this disease.